Immigrant Legal Status and Commute Mode Choice for Hispanics in the United States. Issue 3 (2nd July 2020) - Allen, Ryan; Wang, Jueyu
Abstract: Problem, research strategy, and findings: Despite an estimated 10.7 million undocumented immigrants living in the United States in 2016, little research in urban planning focuses on immigrant legal status. The failure to account for immigrant legal status as an explanatory factor in travel behavior research is problematic because undocumented immigrants face structural disincentives for driving compared with immigrants legally residing in the United States and may make different travel mode choices as a result. We use the 2008 panel of the Survey of Income and Program Participation and a methodology that identifies likely undocumented immigrants in the data to answer two research questions: Given their inability to possess a valid driver's license in most states, do undocumented immigrants drive less than their counterparts who reside in the United States legally? More generally, what is the relationship between immigrant legal status and commuting mode choice? We find that two-thirds of Hispanic undocumented immigrants who commute to work drive, but that undocumented status has a suppressive effect on driving compared with native-born Hispanics or Hispanic immigrants legally residing in the United States. Our analysis does not assess the relationship between travel behavior and immigrant legal status for non-Hispanic immigrants and does not control for built environment factors. Takeaway for practice: Unlicensed driving by undocumented immigrants may reduce public safety. To reduce unlicensed driving by undocumented immigrants, planners should encourage alternative commute modes with a particular focus on carpooling and support the passage of new legislation that allows undocumented immigrants to apply for driver's licenses in states that currently do not give undocumented immigrants this right.